2020
DOI: 10.1002/ajmg.a.61465
|View full text |Cite
|
Sign up to set email alerts
|

Three new patients with Steel syndrome and a Puerto Rican specific COL27A1 mutation

Abstract: Steel syndrome was initially described by H. H. Steel in 1993 in Puerto Rico, at which time he described the clinical findings required for diagnosis. The responsible gene, COL27A1, was identified in 2015 (Gonzaga‐Jauregui et al., European Journal of Human Genetics, 2015;23:342–346). Eleven patients have previously been described with Steel syndrome and homozygous COL27A1 mutations, with eight having an apparent founder mutation, p.Gly697Arg. We describe three more patients identified at Einstein Medical Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Due to the absence of reported consanguinity, which was further verified genetically by the lack of sharing of large segments of homozygosity beyond the region around the COL27A1 gene delineating a common haplotype harboring the c.2089G>C (p.Gly697Arg) variant, at the time we proposed that this variant was the molecular cause of the disease and that it was likely a founder allele in individuals of Puerto Rican ancestry. Since then, we and others [ 5 , 23 ] have confirmed that homozygosity for this missense variant is indeed the molecular defect that causes the skeletal abnormalities observed in STLS.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Due to the absence of reported consanguinity, which was further verified genetically by the lack of sharing of large segments of homozygosity beyond the region around the COL27A1 gene delineating a common haplotype harboring the c.2089G>C (p.Gly697Arg) variant, at the time we proposed that this variant was the molecular cause of the disease and that it was likely a founder allele in individuals of Puerto Rican ancestry. Since then, we and others [ 5 , 23 ] have confirmed that homozygosity for this missense variant is indeed the molecular defect that causes the skeletal abnormalities observed in STLS.…”
Section: Discussionmentioning
confidence: 65%
“…We also performed allele specific genotyping of the c.2089G>C (p.Gly697Arg) variant in suspected Steel syndrome families ascertained since our initial study, including a duo composed of the unaffected mother and her reportedly affected 7-year-old son with clinical and radiological findings of STLS, whom was recently published separately along with other two STLS patients [ 23 ]. The affected proband (BAB8472) was found to be homozygous for the STLS variant and his unaffected mother is, as anticipated, a heterozygous carrier.…”
Section: Resultsmentioning
confidence: 99%